Meningkatkan Kemampuan Kognitif Mengurutkan Bilangan 1-10 Melalui Media Pohon Hitung Anak Kelompok B Di TK Baptis Setia Bakti Kota Kediri - Erlina, Erlina (Universitas Nusantara PGRI Kediri, 2018)
This research is motivated by the observation and experience of the researcher that the cognitive ability, especially the ability to count in counting the number symbols and sorting the number 1-10 is less desirable for the children because of the lack of supporting media. Besides, the teacher has not implemented the fun learning so that the children get bored easily. Media is a means to generate motivation to learn so it is necessary for the development of the ability to count optimally. Based on the background of the problem formulated the problems studied are: Does the use of calculated tree media can improve the cognitive abilities of children, especially in the counting and sorting symbols of numbers 1-10. This study used a collaborative Action Research Class (PTK) approach with a sample of proteges of B TK Baptist Setia Bakti Kota Kediri group of 20 children. The study was conducted in two cycles, using assessments, student observation sheets and teacher observation sheets. The conclusion of this research is: Through study using media of calculating tree proved successful and able to increase cognitive ability counting and sorting symbol of number of 1-10 child of group B. Practical implication of this research result is education objectives in early childhood education unit is preferred in basic skill improvement. To establish strong basic skills, several things are needed, such as the use of Educative Educational aids that interest children. The media of calculating trees is proven to fulfill the objective, so it is expected that PAUD teachers can use it in learning to improve basic capability.